Effectiveness of Project Based Learning in New Normal Era in Term of Math Literacy - M Farid Nasrulloh; Faisol Hidayatulloh; Sony Hidayattulloh; Wisnu Siwi Satiti (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
This research aims to find out the difference in students' mathematical literacy improvement skills by applying learning using Project Based Learning and conventional learning models. Jenins' research is quantitative research. Quantitative research can be defined as a process of finding knowledge by using data in the form of numbers as a tool to analyze information about what you want to know. The subjects in this study were the entire viib class of SMPN 2 Sumobito Jombang. The sample in this study was class VIIB SMPN 2 Sumobito Jombang consisting of 32 students. The instruments used in this study are pre-tests and post tests. Based on the results of the independent test sample t test obtained a significant value of 0.018<0.05 with a confidence level of 95% which means Ho was rejected and Ha was accepted. With the sake of the effect of the Project Based Learning learning model on students' mathematical literacy skills on the results of students' mathematical learning in the statstika material of presentation of class VII data SMPN 2Sumobito Jombang.